Methylation-mediated down-regulation of microRNA-497-195 cluster confers osteogenic differentiation in ossification of the posterior longitudinal ligament of the spine via ADORA2A. Issue 12 (24th June 2020) - Jiang, Anlong; Wang, Nanxiang; Jiang, Yunheng; Yan, Xinxing; Chen, Guanghua; Chi, Hui; Kong, Pengyu; Ren, Hang; Xia, Shiqi; Ji, Ye; Yan, Jinglong
Abstract : Aberrant expression of microRNAs (miRNAs) has been associated with spinal ossification of the posterior longitudinal ligament (OPLL). Our initial bioinformatic analysis identified differentially expressed ADORA2A in OPLL and its regulatory miRNAs miR-497 and miR-195. Hence, this study was conducted to clarify the functional relevance of miR-497-195 cluster in OPLL, which may implicate in Adenosine A2A (ADORA2A). PLL tissues were collected from OPLL and non-OPLL patients, followed by quantification of miR-497, miR-195 and ADORA2A expression. The expression of miR-497, miR-195 and/or ADORA2A was altered in posterior longitudinal ligament (PLL) cells, which then were stimulated with cyclic mechanical stress (CMS). We validated that ADORA2A was expressed highly, while miR-497 and miR-195 were down-regulated in PLL tissues of OPLL patients. miR-195 and miR-497 expression in CMS-treated PLL cells was restored by a demethylation reagent 5-aza-2′-deoxycytidine (AZA). Moreover, expression of miR-195 and miR-497 was decreased by promoting promoter CpG island methylation. ADORA2A was verified as the target of miR-195 and miR-497. Overexpression of miR-195 and miR-497 diminished expression of osteogenic factors in PLL cells by inactivating the cAMP/PKA signaling pathway via down-regulation of ADORA2A. Collectively, miR-497-195 cluster augments osteogenic differentiation of PLL cells by inhibiting ADORA2A-dependent cAMP/PKA signaling pathway.